Use of the Rasch Model in Analyzing Evaluation Questions in End of Year Mathematics Lesson Assessments - Nur Oktapiana, Fuji; Juariah; Kariadinata, Rahayu; Junior Nti, Seth; Sugilar, Hamdan (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2024)
The quality of education in Indonesia still needs to be improved by evaluating on the boutiques and student answer sheets. So this research aims: (1) Clarifying the End of Year Mathematics Lesson Assessments (EYA)'s sheets based on the Bloom's Taxonomy; (2) Counting percentages on the boutiques and the correct answers based on the Bloom's Taxonomy; and (3) Analyze the EYA's grain based on the Winsteps app. This research is a qualitative research with therapeutic methods. Data is the documentation method form 35 boutiques of EYA mathematical subjects and 277 sheets of student answers class VIII in teaching 2021/2022. The research results: (1) There are 11 Lower Order Thinking Skills (LOTS) grains, 16 Middle Order Thinking Skills (MOTS) grains, and 8 HOTS grains; (2) Percentage of grains resulting is 31% of LOTS, 46% of MOTS, and 23% of the HOTS with percentages of the correct answers is 51.5% on LOTS, 42% on MOTS, and 35% on HOTS; and (3) Results of analysis using Rasch model obtained 31 of 35 will have been valid with 4 remaining needs revised, the reliability includes the category is sufficient with the alpha value of 0.72, has a sufficiently diverse level of disassembling, the power of the distinguishing is good, and the effectiveness of its refining has 100% function .